Recognition and Sequencing of Mutagenic DNA Adduct at Single‐Base Resolution Through Unnatural Base Pair - Honglei Wang; Wenchao Tie; Wuyuan Zhu; Shuyuan Wang; Ruzhen Zhang; Jianlin Duan; Bingyu Ye; Anlian Zhu; Lingjun Li (Advanced Science)
Abstract DNA lesions are linked to cancer, aging, and various diseases. The recognition and sequencing of special DNA lesions are of great interest but highly challenging. In this paper, an unnatural‐base‐pair‐promoting method for sequencing highly mutagenic ethenodeoxycytidine (εC) DNA lesions that occurred frequently is developed. First, a promising unnatural base pair of dεC–dNaM to recognize εC lesions is identified, and then a conversion PCR is developed to site‐precise transfer dεC–dNaM to dTPT3–dNaM for convenient Sanger sequencing. The low sequence dependence of this method and its capacity for the enrichment of dεC in the abundance of as low as 1.6 × 10–6 nucleotides is also validated. Importantly, the current method can be smoothly applied for recognition, amplification, enrichment, and sequencing of the real biological samples in which εC lesions are generated in vitro or in vivo, thus offering the first sequencing methodology of εC lesions at single‐base resolution. Owing to its simple operations and no destruction of inherent structures of DNA, the unnatural‐base‐pair strategy may provide a new platform to produce general tools for the sequencing of DNA lesions that are hardly sequenced by traditional strategies.